Physical, Mechanical, and Biological Properties of Silafluofen-treated Tropical Wood Using Multi-Phase Carbon Dioxide Impregnation - Musrizal Muin (Masyarakat Peneliti Kayu Indonesia, 2011)
A new approach in wood preservative treatment using carbon dioxide (CO2) as a carrier solvent has been developed and evaluated its effect on the physical, mechanical, and biological properties of treated tropical wood. It employs CO2 at various combinations of temperatures and pressures in a treatment vessel at once and is called Multi-Phase Carbon Dioxide (MPCO2) treatment. Three commercial tropical wood species (Agathis sp., Palaquium sp., and Heritiera sp.) measuring 1.5 cm (T) x 1.5 cm (R) x 15 cm (L) were prepared for the treatment with a termiticide (silafluofen). A treatment cycle was performed by loading two specimens of each wood species, applying the temperature of 15⁰C and pressure of 60 kg/cm2, gradually increasing the temperature and pressure, respectively, to 35⁰C and 80 kg/cm2, and releasing the pressure to atmosphere. The treatment was conducted with five replicates. Untreated and treated specimens were then evaluated their physical, mechanical, and biological properties. Results show that the MPCO2treatment significantly enhanced the termite resistance of treated wood without any adverse effects on their physical and mechanical properties.A new approach in wood preservative treatment using carbon dioxide (CO2) as a carrier solvent has been developed and evaluated its effect on the physical, mechanical, and biological properties of treated tropical wood. It employs CO2 at various combinations of temperatures and pressures in a treatment vessel at once and is called Multi-Phase Carbon Dioxide (MPCO2) treatment. Three commercial tropical wood species (Agathis sp., Palaquium sp., and Heritiera sp.) measuring 1.5 cm (T) x 1.5 cm (R) x 15 cm (L) were prepared for the treatment with a termiticide (silafluofen). A treatment cycle was performed by loading two specimens of each wood species, applying the temperature of 15⁰C and pressure of 60 kg/cm2, gradually increasing the temperature and pressure, respectively, to 35⁰C and 80 kg/cm2, and releasing the pressure to atmosphere. The treatment was conducted with five replicates. Untreated and treated specimens were then evaluated their physical, mechanical, and biological properties. Results show that the MPCO2 treatment significantly enhanced the termite resistance of treated wood without any adverse effects on their physical and mechanical properties.